Global optimization method for mixed transportation network design problem: A mixed-integer linear programming approach - Luathep, Paramet; Sumalee, Agachai; Lam, William H.K.; Li, Zhi-Chun; Lo, Hong K. (Transportation research. Part B: methodological, 2011)
► Mixed network design problem (MNDP) can be formulated as a mixed-integer linear programming problem (MILP) with the link-based formulation which helps avoiding the path enumeration. ► The global optimality of the approximated MNDP can then be guaranteed following the property of the MILP. ► The proposed algorithm performed well with the tests with small and medium sized networks compared to other existing solution algorithms in the literature. This paper proposes a global optimization algorithm for solving a mixed (continuous/discrete) transportation network design problem (MNDP), which is generally expressed as a mathematical programming with equilibrium constraint (MPEC). The upper level of the MNDP aims to optimize the network performance via both expansion of existing links and addition of new candidate links, whereas the lower level is a traditional Wardrop user equilibrium (UE) problem. In this paper, we first formulate the UE condition as a variational inequality (VI) problem, which is defined from a finite number of extreme points of a link-flow feasible region. The MNDP is approximated as a piecewise-linear programming (P-LP) problem, which is then transformed into a mixed-integer linear programming (MILP) problem. A global optimization algorithm based on a cutting constraint method is developed for solving the MILP problem. Numerical examples are given to demonstrate the efficiency of the proposed method and to compare the results with alternative algorithms reported in the literature.